2012
DOI: 10.1016/j.envpol.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of submicrometer particle dose between Australian and Italian people

Abstract: Alveolar and tracheobronchial-deposited submicrometer particle number and surface area data received by different age groups in Australia are shown. Activity patterns were combined with microenvironmental data through a Monte Carlo method. Particle number distributions for the most significant microenvironments were obtained from our measurement survey data and people activity pattern data from the Australian Human Activity Pattern Survey were used. Daily alveolar particle number (surface area) dose received b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 42 publications
3
42
1
Order By: Relevance
“…However, these values seemed to be lower than typical daily dose values found in previous studies as, for example, values higher than 2 × 10 3 mm 2 ·day −1 were found by [70]. This could be attributed to the selected population of this study, since students are typically less exposed to cooking-generated particles, which are known to highly affect daily particle exposure.…”
Section: Alveolar and Tracheobronchial Particle Dose In The Shs And Bcontrasting
confidence: 51%
See 2 more Smart Citations
“…However, these values seemed to be lower than typical daily dose values found in previous studies as, for example, values higher than 2 × 10 3 mm 2 ·day −1 were found by [70]. This could be attributed to the selected population of this study, since students are typically less exposed to cooking-generated particles, which are known to highly affect daily particle exposure.…”
Section: Alveolar and Tracheobronchial Particle Dose In The Shs And Bcontrasting
confidence: 51%
“…The lung deposited particle surface area concentrations at the mainstream, regardless of the deposition in the lung tract, are extremely higher than particle concentration levels which people are exposed to in typical indoor, outdoor, and occupational environments [49,56,[66][67][68][69][70][71][72], thereby resulting in extremely high doses received by smokers as hereinafter reported.…”
Section: Alveolar and Tracheobronchial Deposited Particle Surface Arementioning
confidence: 99%
See 1 more Smart Citation
“…In reality, the assessment of a person's individual exposurerisk is a complex task, related to a multiplicity of sources, microenvironments and personal lifestyles (Buonanno et al, 2011b(Buonanno et al, , 2012a. For example, in addition to systematically investigated outdoor sources/environments (e.g., trafficrelated and heating-related emissions in urban environments, urban background, rural background, sources in proximity to highway and industrial plants), indoor particle exposure should also be considered along with outdoor aerosol sources.…”
Section: Introductionmentioning
confidence: 99%
“…High frequency measurements of ultrafine particle number concentration (pnc) with mobile sampling devices such as the Philips Nanotracer [8] estimate personal exposure to ufps [3,4,9]. Such devices sample from a location on the person's body, rather than a fixed location in an environment where the person spends a large portion of time.…”
Section: Introductionmentioning
confidence: 99%